„Afera XYZ” jako polityczny dylemat prezydenta Johna Adamsa w świetle relacji Johna Marshalla - Daszynska, Jolanta (Acta Universitatis Lodziensis. Folia Historica, 2001)
So called "XYZ Affair" is not properly known in Polish historiography. This article is an attempt to show some controversial problems connected with it. Needless to say that the American-French relationship was nearly broken, especially after the Washington’s Declaration o f Neutrality, 1793. John Adams, as the second president of the USA was faced with the problems with revolutionary France. He was federalist, but he did not share the opinion of them, especially the High Federalists who wanted a war with France. On the contrary, he organized an extraordinary mission to this country to prevent the war. Up till now this mission is still a very controversial one. Firstly, he men who were to go to France (Charles C. Pinckney, Elbridge Gerry and John Marshall) seemed not to be those whom the Directory might accept. In America they were accepted neither by the Congress, nor by both secretaries of state and treasury. President Adams being aware of the negative opinions about such mission ought to presume that it would not be successful in France. Why then he decided to send those people is still an open question. The other question is connected with the persons known as ”X” ”Y” and ”Z”. The opinion that the Americans did not know them is false. On contrary, they not only knew those men by their names, but they often dined with them and frequently met together. Letters „XYZ” stood then for the really known names. Such a trick was created by Charles C. Pinckney to made the cipher, used in the diplomatic correspondence, not so complicated. Another question if the „XYZ” men were connected with Talleyrand is solved in Marshall’s letters. They unanimously gave us an answer that indeed those people were the men of Talleyrand. The question of a bribe for the Directory was strictly connected with the American relations with the Great Britain. The money given to France were equal with the conflict with Britain. And it was not in the interests of America, especially after Jay’s treaty, 1794. Stanley Elkins’ opinion that the Directory, and especially Talleyrand, were to clever to ask for a bribe is absolutely false, what was proved in this article. On April 3, 1798 president Adams informed Congress about the French demands. This gave the beginning of the affair known as „XYZ” Affair” . The anti-French alitude was very common, straighten by the press. The state of so called „Quasi War” with France forced president Adams to declare Alien and Sedition Acts. Such acts were very unpopular, and in fact, they weakened the Federalist Party. Adams lost his presidential campaign and was defeated by the Republican - Thomas Jefferson.